(untitled) (The International Journal for Scientific Research, 2022)
The treatment of patients experiencing both acute and chronic pain presents unique challenges. While it is challenging to objectively measure a patient’s subjective experience of pain, common misunderstandings about pain medication may dissuade patients from receiving recommended medicine, both of which can lead to insufficient treatment for patients with acute pain. Furthermore, it may be impossible to return to your regular routine when your injury heals if you are ordered to rest in bed for an extended period of time. In contrast, chronic pain treatment involves much more challenges than dealing with an acute pain situation. The essential principles of this approach need to be operationalized to make it possible to generalize statistically the evidence that is to be calculated quantitatively and the huge samples that are to be used with the results. For this reason, the positivist theoretical framework can be accommodated inside the methodology because it integrates the process of theory evaluation. Treatment decisions are frequently misunderstood, leading to unwarranted or even dangerous measures. Those coping with chronic pain would benefit greatly from better understanding the perspectives and intentions of their physicians, which can only be achieved through open lines of communication between patients and medical staff. This publication supports previous suggestions by demonstrating the value of field testing SDM systems before starting a large-scale clinical trial. This study investigates how patients and healthcare providers view chronic pain and how they might best communicate with one another to alleviate it. Future tool developers may benefit from this study and the knowledge acquired from designing and testing technologies with the patient and doctor in mind. Despite the fact that more development and testing are required to fully assess PainAPP’s impact on patients and physicians, the software is already showing promise.